Synthesis of the proposed structure of afzeliindanone - Rita (2020)
A synthesis of the proposed structure of afzeliindanone was achieved by using an alkyne [2+2+2]-cyclotrimerization as a key step. The data for the synthetic material were found not to match those for the natural material, indicating a structural misassignment.